(untitled) - Minasi, Mark (Indianapolis, Ind., 2007)
Learn to install, configure, run, and troubleshoot the professional versions of Vista in this comprehensive new guide from two leading Windows authorities. From Vista's all-new interface, 32-bit/64-bit architecture, and advanced security features to its fantastic new capabilities for audio and video recording, editing, and broadcasting, you’ll get the techniques and task-by-task instruction you need to master this dramatically different OS.
Keywords: Operating systems (Computers),Computer networks,Hệ điều hành (Máy tính),Mạng máy tính